2016
DOI: 10.1021/acs.jctc.6b00602
|View full text |Cite
|
Sign up to set email alerts
|

Urea–Aromatic Stacking and Concerted Urea Transport: Conserved Mechanisms in Urea Transporters Revealed by Molecular Dynamics

Abstract: Urea transporters are membrane proteins that selectively allow urea molecules to pass through. It is not clear how these transporters allow rapid conduction of urea, a polar molecule, in spite of the presence of a hydrophobic constriction lined by aromatic rings. The current study elucidates the mechanism that is responsible for this rapid conduction by performing free energy calculations on the transporter dvUT with a cumulative sampling time of about 1.3 μs. A parallel arrangement of aromatic rings in the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Their results indicate that the interaction of urea with aromatic rings, which may involve both amide-π stacking (Imai et al 2009) and hydrogen bonding, likely to play crucial roles in the urea permeation. Similarly, in a recent computational study on dvUT, phenylalanine ring pairs (Phe190/Phe243 and Phe80/Phe27) were found to be the key residues which involved in stacking interactions with urea molecules inside the pore (Padhi and Priyakumar 2016). understand the correct description of the structure and properties of molecules (Meyer et al 2003;Schottel et al 2008;Waters 2002;Riley and Hobza 2012;Wheeler 2012;Daze and Hof 2012;Macias et al 2003;Ma and Dougherty 1997;Dougherty 2012;Tsuzuki et al 2000a, b;Müller-Dethlefs and Hobza 2000).…”
Section: Urea Conduction Through Membrane Proteinsmentioning
confidence: 88%
See 1 more Smart Citation
“…Their results indicate that the interaction of urea with aromatic rings, which may involve both amide-π stacking (Imai et al 2009) and hydrogen bonding, likely to play crucial roles in the urea permeation. Similarly, in a recent computational study on dvUT, phenylalanine ring pairs (Phe190/Phe243 and Phe80/Phe27) were found to be the key residues which involved in stacking interactions with urea molecules inside the pore (Padhi and Priyakumar 2016). understand the correct description of the structure and properties of molecules (Meyer et al 2003;Schottel et al 2008;Waters 2002;Riley and Hobza 2012;Wheeler 2012;Daze and Hof 2012;Macias et al 2003;Ma and Dougherty 1997;Dougherty 2012;Tsuzuki et al 2000a, b;Müller-Dethlefs and Hobza 2000).…”
Section: Urea Conduction Through Membrane Proteinsmentioning
confidence: 88%
“…A computational study modeled the urea flux in dvUT, the equilibrium urea binding to dvUT, as well as the substitution of urea by DMU in the dvUT (Zhang et al 2017). Another investigation by Padhi and co-workers elucidated the urea permeation mechanism employing umbrella sampling MD simulations (Padhi and Priyakumar 2016). They proposed that urea-aromatic interactions arising from parallelly arranged aromatic rings in the pore lowers the energy barrier for urea transport.…”
Section: Urea Conduction Through Membrane Proteinsmentioning
confidence: 99%
“…Quite interestingly, 38% of the structures containing urea and 25% of those containing urea derivatives were found to fall within the geometric requirements for a stacking arrangement with aromatic rings (e.g., PDB ID: 3IPU and 4EV9). , The relevance of stacking interactions between urea and aromatic side chains in urea transporters (UTs) has been modeled by Priyakumar and co-workers . UTs are trimeric transmembrane proteins with a parallel arrangement of aromatic rings in the pore which allows stacking of urea and urea homologues (e.g., formamide, acetamide, and dimethylurea).…”
Section: Physicochemical Properties Of Ureasmentioning
confidence: 99%
“…The aromatic ring stacking interactions play an important role in urea-assisted protein denaturation. Using Trp-cage miniprotein, Priyakumar and co-workers investigated distortion of the protein hydrophobic core in the presence of urea and showed that aqueous urea optimally solvates aromatic groups in the protein. Furthermore, studies suggested the presence of stacking and NH−π interactions involving aromatic groups and urea.…”
Section: Physicochemical Properties Of Ureasmentioning
confidence: 99%
See 1 more Smart Citation